ANALISIS EFEKTIVITAS PENGELOLAAN DANA ZAKAT BERDASARKAN UNDANG-UNDANG DAN FATWA MUI - Rusdiana Priatna Wijaya; Asril Suwandi (Tathawwur: Jurnal Ekonomi Pembangunan dan Keuangan Islam, 2023)
The purpose of this research was to examine the effectiveness of the distribution of zakat funds at Baitul Maal Tazkia.  The method used is Mixed Method (qualitative and quantitative), which primary data is generated from the observations, direct documentation, interviews with the Chairman or Staff of Baitul Māl Tazkia, and secondary data is from literature studies related to the topic.  The quantitative method that uses the 10th Zakat Core Principle measurement ratio is DCR (Disbursement Collection Ratio). Based on ZCP, the effectiveness of Baitul Maal Tazkia's distribution of zakat funds for 4 years of operation is 55% or is included in the Fairly Effective category (quite effective) where the Disbursement Collection Ratio (DCR) reaches 50-69 percent, with the amount collected during the 2017 to 2017 period.  2020 amounting to Rp 4,536,153,278.  The distribution amount for 2017 to 2020 is IDR 2,472,687,990